Pharyngeal airway changes five years after bimaxillary surgery – A retrospective study - Madhan, Sivaranjani; Holte, Michael Boelstoft; Diaconu, Alexandru; Thorn, Jens Jørgen; Ingerslev, Janne; Nascimento, Gustavo G.; Cornelis, Marie; Pinholt, Else Marie; Cattaneo, Paolo M. (Journal of cranio-maxillo-facial surgery, 2022)
The aim of this study was to retrospectively evaluate pharyngeal airway (PA) changes after bimaxillary surgery (BMS). Preoperative, immediate- and 5-year postoperative cone-beam computed tomography images of subjects who underwent BMS were assessed. The primary outcome variable was the PA volume. The secondary outcome variables were the retropalatal and oropharyngeal volumes, cross-sectional area, minimal hydraulic diameter, soft tissue, skeletal movements and sleep-disordered breathing (SDB). A total of 50 patients were included, 33 female and 17 male, with a mean age of 26.5 years. A significant increase in the PA volume was seen immediately after surgery (40%), and this increase was still present at 5-year follow-up (34%) (P < 0.001). A linear mixed model regression analysis revealed that a mandibular advancement of ≥5 mm (P = 0.025) and every 1-mm upward movement of epiglottis (P = 0.016) was associated with a volume increase of the oropharyngeal compartment. Moreover, ≥5-mm upward movement of hyoid bone (P = 0.034) and every 1-mm increase in minimal hydraulic diameter (P < 0.001) correlated with an increase of the PA volume. A total of 30 subjects reported improvement in the SDB at 5-year follow-up. This study demonstrated that BMS led to an increase in PA dimensions in non-OSA patients, and these changes were still present at 5-year follow-up. BMS seemed to induce clinical improvement in SDB.